Design A Medical Device Sales Information System at PT. Pilar Manunggal Asia Jakarta - Siti Nurajizah (Institute of Computer Science (IOCS), 2022)
PT. Pilar Manunggal Asia Jakarta is a company engaged in the sale of medical device products. In the process of selling it is still Using a manual sales system, namely sales transactions are carried out directly by coming to the company. Promotions carried out are also still in the form of information from brochures, pamphlets and banners this makes sales turnover less significant and sales have not been effective and efficient. Based on these problems, an information system is needed that can help the company in the sales process. This study used the waterfall method as a software development which is often called the linear sequential model or classic life flow. The information system for the sale of medical devices made is website-based. The use of the website can increase sales and for consumers it is easy to make transactions in real time.